Sistem Demokrasi: Marketing Politik dan Jaminan Kebeneran Informasi - POERWADI, HEROE (Universitas Muhammadiyah Yogyakarta, 2011)
The style of liberal democratic system of individualism, was more apparent on the implementation ofthe Indonesia elections in 2009. Those could be observed by the implementation of multi-partysystem, direct election system, the value system of one person one vote and one value, and culminatedin the determination of legislative candidates by majority vote. As the consequency of the system,more campaigns held by personal than the political parties occurred in election 2009. Theimplications of the pattern of liberal individualism, increasingly the candidates took most of politicaladvertising as the mass campaign media, in streets, mass media and public places. Strategicbusinesses like in the real business marketing industry was used to promote the candidates andpolitical parties as a media to get as many voter as possible. In fact the implementation was distorted,the candidate only presented their personal popularity, but not the program they had. Moreover, theyplaced more the image performance, position highly than the commitment and personal integrity.Additionally, considerable segmentation techniques was had more pay attention than doingcommunication with people.